Influence of air raid sounds on the stress level of schoolchildren of Ukraine (Environment & Health, 2025)
On 24 February 2022, most Ukrainians felt the real sounds of war (air raids, shelling, explosions) and found themselves in new, unfamiliar living conditions with an altered psycho-emotional state against the background of the body's stress reactions. Studying the conditions of children’s life, lifestyle and quality of life during armed aggression, as well as the influence of these factors on health and adaptation is a pressing challenge.The aim of the study was to analyze the reactions of school-age children to the sounds of air raid alarms.Materials and methods: In April-June 2024, a survey of parents of school-age children was conducted in 103 secondary schools in all regions of Ukraine. The QRAPH questionnaire, modified for martial law, collected demographic, anthropometric, and lifestyle data, morbidity and migration patterns, as well as schoolchildren's stress levels. The presence of anxiety and depression symptoms was determined by the RCADS-P-25 scale. Statistical processing was performed using R-Studio.Results: The study showed that one third of schoolchildren have an average level of stress at the sound of air raid sirens, and high and low levels of stress are (16.3±0.9)% and (13.9±0.9)%, respectively. Schoolchildren with chronic diseases, as well as with symptoms of anxiety and depression, reacted more acutely to the sounds of sirens (χ2=13.8; p=0.008 and χ2=52.2; p
Keywords: school-age children; parents; air raid alarm sounds; subjective stress level